2017
DOI: 10.1590/s1678-86212017000300166
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of slab-on-grade heat transfer in EnergyPlus simulation program

Abstract: Resumo O fluxo de calor entre o piso e o solo de uma edificação térrea é um dos aspectos mais influentes em seu desempenho térmico e energético. No entanto, há ainda um grande número de incertezas e poucos estudos nessa área. Neste trabalho comparam-se diferentes alternativas de modelagem nos programas EnergyPlus (8.5.0) e Slab (.75) dos parâmetros relacionados à transferência de calor entre o piso e o solo, e sua influência no desempenho térmico de uma edificação térrea naturalmente ventilada, localizada em S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The results measured for a critical summer day indicated that while the external air temperature reached the maximum value of 43 ºC, the internal temperature of the upper deck registered about 40 ºC and the basement temperature reached the maximum value of 35 ºC. In Brazil, Costa, Roriz e Chvatal [6] compared different modeling alternatives of the parameters related to the heat transfer between the floor and the ground, and their influence in the thermal performance of a naturally ventilated single-story house, using the programs EnergyPlus/GroundDomain e EnergyPlus/Slab. The thermophysical properties of the soil were the data that had the most influence.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results measured for a critical summer day indicated that while the external air temperature reached the maximum value of 43 ºC, the internal temperature of the upper deck registered about 40 ºC and the basement temperature reached the maximum value of 35 ºC. In Brazil, Costa, Roriz e Chvatal [6] compared different modeling alternatives of the parameters related to the heat transfer between the floor and the ground, and their influence in the thermal performance of a naturally ventilated single-story house, using the programs EnergyPlus/GroundDomain e EnergyPlus/Slab. The thermophysical properties of the soil were the data that had the most influence.…”
Section: Introductionmentioning
confidence: 97%
“…The heat flow between the floor and the ground of a single-story building is one of the most influential aspects in its thermal and energy performance [6]. For this reason, basements must be conditioned to meet the same thermal comfort criteria as the other spaces on the upper floors of residences [1].…”
Section: Introductionmentioning
confidence: 99%